Desa Cerdas dan Inovasi Pelayanan Publik di Masa Endemi: Belajar dari Desa Mojowarno - Addiansyah, Muhammad (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2024)
Endemic and the incessant development of technology and information have had a new impact on governance. This paper provides evidence of how the village government is able to adjust to this. The adaptation process, although it takes a long time, can be successfully carried out. Various advantages such as effective leadership, competent village officials to technologically literate people are supporting factors for the implementation of smart villages in this village. Our research method is a qualitative method with data collection techniques, namely primary data with interviews and secondary data. Primary data collection was carried out by means of interviews while secondary data collection was carried out by collecting data available online, either through websites or social media. There are several reasons why smart villages can be developed in Mojowarno Village, including: the leadership of the village head who is very persistent, then the creativity of village officials and the third, namely the majority of people who are already literate in technology. On the basis of this argument, public service innovations in Mojowarno Village can continue.